Education and the alterity of democracy - Stevenson, Nick (Fundacao Carlos Chagas, 2018)
The idea of a democratic education in the English context has lost a considerable amount of ground since the 1960s. Here I argue that such is the dominance of neoliberal understandings of education over the Right and much of the social democratic Left that new thinking is required. I begin by considering the view that we have now become so post-democratic that people no longer wish to be free. It is in this context that we may talk about the alterity of democracy. I explore different ideas about how we might seek to link education to ideas of the commons, thereby connecting the idea of education to more participatory notions of citizenship. All of these ideas need to be revived in the context of a state that increasingly controls schools from the center and the dominant rationality of the market.